Investigating the Problem of Recast Feedback in Grammar Instructions - Rahmatul Jannah; Noviana Hanani; Gina Amalia Shalehah; Md Noor Saper (International Journal of Education, Information Technology, and Others, 2022)
Recast feedback is an example of feedback, which is an essential component of any educational experience. Feedback is an essential component of any educational experience. Recast is a kind of corrective feedback in which the instructor either explicitly demonstrates that the student's speech was erroneous, tacitly reformulates the student's mistake, or provides a proper answer. However, there is a potential issue with utilizing recast as a means of providing feedback. It is necessary to investigate the issue in order to locate it in order to determine what the problem is. A Grammar instructor and five students from the Antasari State Islamic University of Banjarmasin are the participants in this research. The university is located in Banjarmasin, Indonesia. Interviews with the participants will be conducted so that information may be gleaned regarding their experiences with recast feedback. According to the findings of the inquiry carried out by the researcher, there are a number of issues with recasts feedback.